2021
DOI: 10.1016/j.cmet.2021.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Excessive exercise training causes mitochondrial functional impairment and decreases glucose tolerance in healthy volunteers

Abstract: Highlights d Here, we investigate the dose-response effects of exercise training in healthy subjects d Excessive exercise training induces substantial mitochondrial respiratory impairment d Mitochondrial impairment is associated with impaired glucose tolerance d Despite excessive training, markers of global oxidative stress were unchanged

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 66 publications
(68 reference statements)
9
142
0
4
Order By: Relevance
“…In support of this argument, it has been recently demonstrated that regular, moderate to vigorous physical activity reduced the risk of community-acquired infectious diseases and infectious disease mortality [ 82 ]. All in all, it should be noted that exhaustive and excessive exercise training may cause mitochondrial functional impairment, inducing a dysregulated systemic inflammatory response, thus being detrimental for health [ 83 , 84 , 85 ]. Hence, individually tailored exercise prescriptions among people with post-COVID-19 are essential to elicit positive adaptive changes to enhance immune function.…”
Section: The Potential Role Of Exercise In Post-covid-19 Syndromementioning
confidence: 99%
“…In support of this argument, it has been recently demonstrated that regular, moderate to vigorous physical activity reduced the risk of community-acquired infectious diseases and infectious disease mortality [ 82 ]. All in all, it should be noted that exhaustive and excessive exercise training may cause mitochondrial functional impairment, inducing a dysregulated systemic inflammatory response, thus being detrimental for health [ 83 , 84 , 85 ]. Hence, individually tailored exercise prescriptions among people with post-COVID-19 are essential to elicit positive adaptive changes to enhance immune function.…”
Section: The Potential Role Of Exercise In Post-covid-19 Syndromementioning
confidence: 99%
“…Hormesis following exercise has been suggested to promote healthy brain aging [ 77 ]. According to the nature of hormetic effects, however, doses of exercise that are too high have been shown to be detrimental for mitochondria [ 78 ], further discussed in an associated editorial [ 79 ].…”
Section: Improving Mitochondrial Functions By Exercise In Skeletal Musclementioning
confidence: 99%
“…During the fourth week of the program subjects reached 5 HIIT sessions per week at 8 min intervals with intensity of 90% of VO 2 max and 3 min of rest between intervals [65]. After the fourth week disturbances in mitochondria function and impaired glucose homeostasis were observed [65]. It could be speculated that in the case of some of patients in the current study who were unable to complete this was related to the intensity of IAP.…”
Section: Relationship Of Peak Oxygen Uptake Improvement and Mitofusin1 Levelmentioning
confidence: 72%
“…Interestingly, both IAP and GET in the PACE trial [51] programmes consisted of five training sessions per week. In contrasts, five HIIT sessions per week has been used to intentionally induce overreaching in healthy participants [65]. We suggest that further studies should consider a personal medicine approach to distinguish whether activity could be considered at all in individual CFS patients.…”
Section: Relationship Of Peak Oxygen Uptake Improvement and Mitofusin1 Levelmentioning
confidence: 99%
See 1 more Smart Citation